Constitutional Jurisdiction and Criminal Justice: Issues and Prospects - San Martín Castro, César (2004)
There is no doubt that case law plays a fundamental role in the interpretation and application of the law. However, a number of problems remain. One of them is the possible tension between constitutional and ordinary jurisdiction. With this in mind, the author undertakes an in-depth reflection on the role of jurisprudence in the national legal system, with particular emphasis on the constitutional and criminal contexts. In order to do so, it is necessary to first address two essential points: (i) to define the constitutional function and jurisprudence and its relationship with the ordinary jurisdiction; and (ii) to understand that, despite the existence of a link between one jurisdiction and the other, we are talking about two different models. Once the picture has been clarified, it can be understood that criminal law is subsumed within the constitutional framework, which is subject to the issuance of rulings that ensure coherence between the principles established in criminal law and the Constitution.